MORTALITY PREDICTORS FOLLOWING DEFINITE SUBACUTE STENT THROMBOSIS: REAL-WORLD EVIDENCE FROM THE LARGEST PRIMARY PCI PROGRAM IN SOUTH ASIA (Journal of Medical & Health Sciences Review, 2026)
Background: Subacute stent thrombosis (SAST) is a significant complication that occurs after the introduction of percutaneous coronary intervention (PCI) with stent implantation, resulting in a high mortality rate, especially in high-risk groups. This paper aims to examine mortality predictors after SAST in South Asian patients using real-world data from the biggest primary PCI program in the area.Objective: To identify key predictors of mortality in patients with definite subacute stent thrombosis following primary percutaneous coronary intervention in a South Asian population.Methods: The study was a retrospective cohort study, which was conducted at one of the major tertiary care hospitals in South Asia, and included patients undergoing PCI between August 2024 and November 2024. Three hundred and eighty patients who were known to have SAST were involved. The hospital PCI registry was used to gather data about the demographics, clinical risk factors, procedural history, and outcomes. Predictors of mortality were determined by multivariate logistic regression.Results: Old age, diabetes, hypertension, and lack of adherence to dual antiplatelet therapy (DAPT) were found to be important predictors of mortality. Diabetic patients were found to have over 2 times the risk of death compared to non-diabetics. The bare-metal stent implantation was linked to a greater occurrence of subacute thrombosis than the drug-eluting stent, but the risk of both types of stents remained.Conclusion: The research identifies major mortality predictors after subacute stent thrombosis, such as age, diabetes, hypertension, and adherence to DAPT. These results underscore the importance of specific management approaches and better compliance with treatment plans in order to decrease the death rates among high-risk groups undergoing PCI in South Asia.